Why can China maintain a high crop diversity? A spatial-temporal dynamic analysis. (April 2022) - Liu, Zhenhuan; Tang, Guoping; Zhou, Yi; Sun, Jing; Wu, Wenbin; Yang, Peng
Crop diversity is crucial for producing more food and nutrition in the crowded planet and achieving agricultural sustainable development, and thus it is a hot topic in shaping policies aimed at ensuring food security. Many studies have revealed that enhanced crop diversity can benefit crop productivity. However, research on how to maintain a relatively high crop diversity at regional and national scales remains limited. This study attempts to examine the underlying mechanisms of crop diversity changes in China and eventually answer why China can maintain a high crop diversity from the spatial-temporal perspective. To achieve this end, the county level crop area dataset for the period of 1980–2014 was compiled and used to quantify the spatiotemporal dynamics of crop diversity in China. The result reveals that the China's crop diversity trended upward over past 35 years, evidenced by more than 7 major crops at national level and 4 major crops at county level having undergone massive planting process to maintain a high crop diversity. Spatially, the crop diversity increased in more than two-thirds of the counties, and its hotspots moved gradually to the south-west mountainous area. The natural factor of slope and the social factor of population density contributed to shape the crop diversity pattern in global effects. In contrast, the irrigation degree, elevation of cropland, mean annual temperature and precipitation affected the spatially non-stationary distribution of crop diversity at the local level. On the whole, the maintenance of a higher crop diversity in China not only was limited by natural conditions, but also subject to adopt the multi-cropping systems strategic choice for the country to agricultural conditions. We argued that crop diversity can be an indicator to draw agricultural zoning, and increasing crop diversity should be recognized as a policy tool to implement agricultural sustainable development strategy.